PERANCANGAN APLIKASI PEMAINAN “BISINDOKU”SEBAGAI MEDIA KOMUNIKASI PENGENALAN BAHASA ISYARAT - Lana Duwi Saputra; Ricky Widyananda Putra (Kartala Virtual Studies, 2024)
Indonesian Sign Language (BISINDO) is a non-verbal communication system used by the deaf and speech impaired community in Indonesia. In recent years, the use of technology has grown rapidly, including the use of technology in education in the form of alternative media for educational games. The problem encountered in this creation was in the form of communication patterns that were less effective for the community towards deaf and speech impaired friends. This creation aims to teach the importance of Indonesian Sign Language (BISINDO) as a form of communication pattern with deaf and speech impaired friends. This study uses a theory UI & UX design. Meanwhile, the creation method uses field observations, literature studies and interviews with informants. Designing this game, the results obtained from its creation are contributing to expanding understanding of the potential for using BISINDO as a means of communication in the realization of educational games. It is hoped that the creation of the BISINDO game can inspire game developers, especially educators, to consider and implement Indonesian Sign Language in the development of inclusive educational games.